The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.4141/cjss2011-048
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and redistribution of residual chloride, nitrate, and soil test phosphorus in soil profiles amended with fresh and composted cattle manure containing straw or wood-chip bedding

Abstract: Miller, J. J., Beasley, B. W., Drury, C. F. and Zebarth, B. J. 2011. Accumulation and redistribution of residual chloride, nitrate, and soil test phosphorus in soil profiles amended with fresh and composted cattle manure containing straw or wood-chip bedding. Can. J. Soil Sci. 91: 969–984. Limited research has compared the effect of fresh versus composted beef (Bos taurus) cattle feedlot manure containing straw or wood chips on accumulation and redistribution of residual chloride (Cl), NO3-N, and soil test P (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…1 For calculating the linear relationships between P balance in kg ha −1 yr −1 and change in STP concentration in mg P kg −1 yr −1 , one value from Stumborg and Schoenau (2008) with a high P balance of 164 kg P ha −1 yr −1 was excluded from the analysis. Similarly, for the modified Kelowna soil test, P balances greater than 300 kg P ha −1 yr −1 were also excluded [see, for example, Miller et al (2011) and Olson et al (2010)]. These data were excluded because they were much higher than the P balances observed for the SLCs in those regions and were affecting the fit of the linear relationship for the range of interest.…”
Section: Estimated Soil Test P Calculationmentioning
confidence: 99%
“…1 For calculating the linear relationships between P balance in kg ha −1 yr −1 and change in STP concentration in mg P kg −1 yr −1 , one value from Stumborg and Schoenau (2008) with a high P balance of 164 kg P ha −1 yr −1 was excluded from the analysis. Similarly, for the modified Kelowna soil test, P balances greater than 300 kg P ha −1 yr −1 were also excluded [see, for example, Miller et al (2011) and Olson et al (2010)]. These data were excluded because they were much higher than the P balances observed for the SLCs in those regions and were affecting the fit of the linear relationship for the range of interest.…”
Section: Estimated Soil Test P Calculationmentioning
confidence: 99%
“…Nutrient build-up can be prevented by applying manure to meet the P, rather than N, requirements of the crop or haying manure-amended grasslands rather than grazing (Olson et al 2010;Wilson et al 2011). Including a high-C substrate, such as wood chips, in manure can also reduce N loading to the system (Miller et al 2011). Incorporating manure into soil reduces volatilization of N (Schoenau and Davis 2006) and nutrient losses to surface water (Jokela et al 2012).…”
Section: Animal Manure and Compostmentioning
confidence: 99%
“…Manure application at high rates and/or frequency can result in nutrient accumulation in soils, contamination of surface and ground water, and increased GHG emissions (Stumborg and Schoenau 2008;Ashjaei et al 2010;Miller et al 2010Miller et al , 2011Miller et al , 2012. Appropriate management practices such as those described by Shoenau and Davis (2007) and others can effectively mitigate the potential for nutrient loss and environmental contamination.…”
Section: Animal Manure and Compostmentioning
confidence: 99%
“…Historically, manure application rates in North America and Europe have been based on crop N requirements to meet yield potentials (Miller et al 2011). The imbalance between N and phosphorus (P) requirements of the crop and the supply of these nutrients in manure has led to two different manure application strategies, namely N-based and P-based (Olson et al 2010a(Olson et al , 2010b.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of greater N:P uptake ratio of crops than the N:P ratio in manure, N-based manure management results in the accumulation of P (Eghball 2002). Intermittently applying manure by supplying several years of crop P demand is more cost effective in labour and equipment compared with annual P-based manure application (Miller et al 2011). Eghball and Power (1999) reported that P-based manure or compost application resulted in similar corn grain yield to those of N-based treatments but had significantly less soil available P level after 4 yr of application.…”
Section: Introductionmentioning
confidence: 99%